Resisting Radical Rebels: Variations in Islamist Rebel Governance and the Occurrence of Civil Resistance - Bamber, Matthew (Terrorism and political violence, 2023)
During the Syrian civil war, different types of Salafi-Jihadi rebel groups controlled territory and established governance over civilians. Their governing strategies have been markedly diverse. In this study, we explore how this governance variation can help to explain the occurrence of civil resistance. We suggest that different types of rebel governance structures provide political opportunities for civilians to mobilize against those rebel groups through public demonstrations. In particular, we argue that it is middle-ranged opportunity structures of rebel governance that strongest incentivizes civil resistance, by giving enough space for civilian mobilization but fewer alternative channels of expressing discontent. This argument is explored through an analysis of the variation between the three main Salafi-Jihadi rebel groups in Syria—IS, HTS and Ahrar al-Sham. We show how differences in the groups’ four rebel governance dimensions—rebel collaboration, civilian inclusion, alliance structure, and repression—impact the political opportunities for civilians to mobilize against these groups. We find that HTS, the group that is in the middle range across these four governance dimensions, provided greater opportunity for civilian protests. This study uses a new dataset of civilian resistance events in Syria as well as interviews with civilians governed by these groups.